2023
DOI: 10.1371/journal.pone.0279734
|View full text |Cite
|
Sign up to set email alerts
|

Association between abdominal obesity and diabetic retinopathy in patients with diabetes mellitus: A systematic review and meta-analysis

Abstract: Objective Previous studies have reported different opinions regarding the association between abdominal obesity and diabetic retinopathy (DR) in patients with diabetes mellitus (DM). In this study, we aimed to investigate this problem through a systematic review and meta-analysis to provide a basis for clinical interventions. Methods A comprehensive search was conducted in the PubMed, Embase, and Web of Science databases up to May 1, 2022, for all eligible observational studies. Standardized mean differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…As the rising burden of type 2 DM is a major concern in worldwide healthcare, the utility of weight loss, bariatric surgery, and novel antidiabetic drugs to improve comorbidities have been increasingly studied. Early worsening of DR is a documented paradoxical phenomenon that follows rapid, intensive correction of HbA1c [2 ▪▪ ,8 ▪ ,9,10]. While intensive glycemic control may exhibit short-term retinopathy progression, it still emerges as a favorable strategy in the long-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the rising burden of type 2 DM is a major concern in worldwide healthcare, the utility of weight loss, bariatric surgery, and novel antidiabetic drugs to improve comorbidities have been increasingly studied. Early worsening of DR is a documented paradoxical phenomenon that follows rapid, intensive correction of HbA1c [2 ▪▪ ,8 ▪ ,9,10]. While intensive glycemic control may exhibit short-term retinopathy progression, it still emerges as a favorable strategy in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…In this same study, overweight participants randomized into lifestyle intervention counseling (including increased physical activity, fiber intake >15 g/1000 kcal, and 30% decrease in dietary fat intake) over a mean of 4 years demonstrated significantly decreased retinal microvascular abnormalities [odds ratio (OR) 0.52, P = 0.039] [7]. Other multivariable type 2 DM analyses demonstrate that the distribution of adipose tissue, especially abdominal obesity, was more closely associated with DR prevalence and severity than relative BMI [8 ▪ ]. The U.S. Diabetes Prevention Program Outcomes Study has challenged this association.…”
Section: Weight Loss and Diabetic Retinopathymentioning
confidence: 99%
“…17,18,24 Nevertheless, the relationship between WC, the most commonly used parameter of abdominal adiposity, and DMC remains unclear. [24][25][26] Recent pooled analysis, largely of cross-sectional data, showed a positive association of WC with DN and DR. 57,58 This is, however, probably subject to the limitations mentioned above, including the time-varying confounding bias.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Sweden showed that in T1DM and T2DM patients, the occurrence of DR was correlated with a high BMI [ 142 ]. It was also shown that abdominal obesity measured by waist circumference (WC) and waist-to-hip ratio (WHR) was positively associated with DR in patients with T1DM and T2DM [ 143 , 144 ]. Waist circumference (WC) was higher in patients with DR than in patients without DR.…”
Section: The Role Of MD In the Treatment And Prevention Of Obesity An...mentioning
confidence: 99%
“…Waist circumference (WC) was higher in patients with DR than in patients without DR. Similarly, the waist-to-hip ratio (WHR) was higher in patients with DR than in patients without DR [ 144 ]. However, no correlation was found between abdominal obesity and the severity of diabetic retinopathy [ 144 ].…”
Section: The Role Of MD In the Treatment And Prevention Of Obesity An...mentioning
confidence: 99%